STRATEGI KOMUNIKASI TIM PUBLIKASI SUBKOMISI MEDIA BARU DALAM MEMPERBAIKI CITRA LEMBAGA SENSOR FILM RI (Studi pada Akun Instagram @lsf_ri) - Yunisa Adiestiya, (2021)
Since Lembaga Sensor Film RI established in 1916, it has been known as 'film cutter, the role as censoring film is useless' which has bad impact for LSF's corporate image that tends to be negatives. This means public or many people do not understand about duties and role of LSF. Improving the negative image of the institution is very important because it will affect the existence and trust of the public. With research and developing a communication strategy will make it easier to choose the step in improving corporate image. The purpose of this study was to find out about how communication strategy that used by Publication Team New Media Sub-commission. This study used a qualitative descriptive method. The result is with a message delivery method on content aspect, educative and informative in improving image of Lembaga Sensor Film RI through social media Instagram @lsf_ri supported by attractive visuals and related content to film, censorship, and LSF for educate and fulfill public information needs. Most of the news recapitulation is about LSF activities (webinars, visits, press conferences, and other positive activities). Keywords: Communication Strategy, Image, Social Media, Instagram.